Visual Novels as Anxiety Interventions: Visual Storytelling and Emotional Engagement in Young Adults - Alexandra, Juliette (Journal of Visual Communication Design, 2026)
Anxiety disorders are a common mental health challenge experienced by young adults, especially university students who face academic pressure and tend to overthink. Visual novel is a narrative-based interactive media that has potential to help users understand and manage their emotions, thought, and reflect on their coping styles through an immersive and more personal gaming experiences. This study aims to identify and design visual novel design principles that support adaptive coping mechanism strategies for young adults. The focus is directed toward visual storytelling, and emotional interactive experiences as design elements that can help users manage anxiety in a more empathetic and intuitive way. This study uses a qualitative method with data obtained through a literature review, interviews with a psychology expert, and three young adults aged 21-22 who enjoy playing visual novel games to better understand their visual preferences and responses toward coping systems in game. Furthermore, an analysis of the narrative and visual elements within visual novels was conducted. The findings reveal that the application of adaptive coping mechanisms, particularly problem-focused coping and positive reappraisal in dialog choice systems, are proven to be able to increase players understanding of healthy coping strategies and encourage them to reflect on their efforts to deal with anxiety in everyday life. Respondents also stated that the use of cute art style and soft pastel colors created a calming atmosphere for players, making the gaming experience more comfortable without causing excessive stress or tension. Interactive narration also contributes to increased emotional engagement, which supports players in reflecting on the consequences of their choices. Therefore, visual novels have the potential to serve as entertainment media that are not only attractive but also effective in helping young adults recognize coping mechanisms as a form of anxiety intervention. However, further research is still needed by involving more respondents and conducting long-term effectiveness testing to assess the application of adaptive coping in real life through visual novel games.